Kinerja, Struktur Keuangan, dan Praktik Perataan Laba: Studi Empiris pada Perusahaan Consumer Cyclical 2020-2024 - Angelia Fernanda; Katarina Agnes (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
The main focus of this study aims to observe the impact of performance, financial structure, and income smoothing practices: an empirical study of consumer cyclical companies from 2020 to 2024. The secondary data utilized in this study was derived from the companies' annual financial reports. The population includes all consumer cyclicals companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. The sample of this research used purposive sampling, based on criteria pertinent to the research goals. The sample size consisted of 15 firms throughout a five-year timeframe, obtaining a sample total of 75. In this research SPSS version 27 software was utilized to assist in the data analysis process, and the method used to analyze correlation between variables is logistic regression. The findings indicate that the variables of cash holding, debt to asset ratio and net profit margin simultaneously has a significant impact on income smoothing. Partially, cash holdings and debt to asset ratio do not affect income smoothing, while net profit margin has a significant negative effect on income smoothing.